Managers as key players in HR transformations: Importance of manager involvement for successful HR transformation implementation - Junttila, Roosa (My University, 2019)
Managers are the link between the HR strategy and the employees and hence the way they interpret and execute the tasks and decision making related to HR matters affects the effectiveness of the HR operating model. The business environment is constantly evolving due to e.g. digitalization and the HR function must develop accordingly. Thus, HR transformations, in which the whole HR operating model is renewed, are more and more common and companies need to be able to exploit the benefits of these changes. Existing research highlights the importance of managers’ role for successfully functioning HR operating models, but there is a lack of research on manager involvement in HR transformations. Most of these projects are too HR-driven, as the key to success is in fact in involving the people leaders and letting their point of view guide the transformation. Hence, the aim of the research was to define how the managers can be more involved in these projects so that their opinions and input is utilized to create even more successful HR transformations. A case study was conducted by interviewing ten managers and three HR leaders in a company in which a global HR transformation had just been implemented. A practical model for successful HR transformation projects was created with the focus on manager point of view. A market test was then conducted by asking HR professionals to evaluate the credibility and usability of the model in case it would be utilized to guide an actual project. The findings confirm that manager involvement is critical in implementing the new HR operating model. They must be involved throughout the project in order to ensure commitment and avoid resistance to change. Even just giving them the opportunity to make their own decision about whether to participate or not increased their engagement and positive attitude towards the project. The market test was also successful, indicating that the HR professionals would see the model as beneficial if utilized to guide an HR transformation.
Keywords: HR transformation; change management; managers’ HR role; participation; fi=Johtaminen ja organisaatiot|en=Management and Organization|; fi=Henkilöstöjohtamisen maisteriohjelma|en=Master's Programme in Human Resource Managment|